Color tuning of Eu-Tb co-doped borophosphate glasses for white light through valence state adjustment - 徐所成 郑玺 田华 吕天帅 王鹏 王达健 (Optoelectronics letters, 2011)
The dependence of color points of white light on the composition of bomphosphate glasses co-doped with europium （En） and terbium （Tb） has been investigated in terms of valence change of rare earth ions. Under ultraviolet （UV） excitation, the white light is observed to be from a combination of 4f65d → 4f7 band transition emission at 425 nm for Eu^2＋, 5D0 → ^7Fj （J= 1, 2） lineemissions at 593 nm and 611 nm for Eu^3＋, and 5D4 → 7F5 band transition emission at 545 nm for Tb^3＋. By varying the glass composition, the resultant emission color can be tuned efficiently. Eventually, the optimized white light with commission international de I＇Eclairage （CIE） coordinate of （0.3382. 0.2763） and the correlate color temperature （CCT） at 5010 K are achieved.